Tinjauan Implementasi Kebijakan Listrik Pedesaan di Desa Semembang dan Desa Sanglar, Kecamatan Durai Karimun - Septian, Doni Septian; Rahmadeni, Yozi (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2024)
This research aims to examine the implementation of rural electrification policies in Desa Semembang and Desa Sanglar, Kecamatan Durai, Karimun, as well as the influencing factors. The research employed a descriptive approach with a qualitative method, utilizing data collection techniques such as interviews and documentation. Research informants included the Head of the Electricity Sector, members of the Regional People's Representative Council (DPRD) of the Kepulauan Riau Province, the Secretary of UP3 Manager and UP2K Manager of PLN Tanjungpinang, Village Heads, Village Consultative Council (BPD) members, youth representatives, and community leaders in Desa Semembang. Data analysis was conducted in reference to the policy implementation theory by Van Meter and Van Horn. The research findings indicate that although electricity development in Desa Semembang and Desa Sanglar has been initiated, its implementation has not reached its maximum potential. This is attributed to various challenges, including: 1) a policy shift from acquiring new machines to machine relocation, 2) transportation challenges in the machine relocation areas, 3) a limited number of available operators for the operational area, 4) financial resource constraints due to budget refocusing during the COVID-19 pandemic, 5) communication misunderstandings between the Department and the villages, and a lack of political support from the Legislative bodies of the Province and District within the sub-district's electoral district.